Wavelength-selective orbital angular momentum generation based on a plasmonic metasurface. Issue 24 (6th June 2016) - Yang, Kunpeng; Pu, Mingbo; Li, Xiong; Ma, Xiaoliang; Luo, Jun; Gao, Hui; Luo, Xiangang
Abstract : Wavelength-selective orbital angular momentum of light with two different topological charges has been achieved by a plasmonic metasurface. Abstract : Nanoapertures with space-variant geometries are designed in a gold thin film to construct an ultrathin plasmonic metasurface, which has been demonstrated both numerically and experimentally to selectively generate and focus orbital angular momentum (OAM) beams with different topological charges at the wavelengths of 930 nm and 766 nm, respectively. Moreover, the interference patterns between the different circularly polarized transmission light were used to confirm the topological charges unambiguously. The agreement between the simulated and measured results suggests that the metasurface of wavelength-selective OAM modes may have potential applications in future optical communication systems.